2021
DOI: 10.1039/d1ma00376c
|View full text |Cite
|
Sign up to set email alerts
|

Flexible electrochromic devices prepared on ultra-thin ITO glass

Abstract: Electrochromic devices (ECDs) containing iron-based metallo-supramolecular polymers (Fe-MEPE) and Prussian blue (PB) as active electrode materials, a polymer electrolyte and flexible ultra-thin indium tin oxide (ITO) glass as transparent conductive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The use of ultrathin glass as the substrate for electrochromic application has been recently investigated by Schott et al and was the only reported example to date. [59] Unlike ITO on polymer substrates, which would usually give very different properties than its glass counterpart, ultrathin ITO glass offer a new possibility to directly transfer the electrochromic performance from a rigid device to a flexible one. To demonstrate the compatibility of the ultrathin glass with the ionogel, a curved eyes protector has been fabricated as shown in Figure 5a,b which exhibited essentially similar spectroelectrochemical performance as the rigid P-WO 3 device (Figure S19, Supporting Information).…”
Section: Flexible Electrochromic Eye Protector and Displaysmentioning
confidence: 99%
“…The use of ultrathin glass as the substrate for electrochromic application has been recently investigated by Schott et al and was the only reported example to date. [59] Unlike ITO on polymer substrates, which would usually give very different properties than its glass counterpart, ultrathin ITO glass offer a new possibility to directly transfer the electrochromic performance from a rigid device to a flexible one. To demonstrate the compatibility of the ultrathin glass with the ionogel, a curved eyes protector has been fabricated as shown in Figure 5a,b which exhibited essentially similar spectroelectrochemical performance as the rigid P-WO 3 device (Figure S19, Supporting Information).…”
Section: Flexible Electrochromic Eye Protector and Displaysmentioning
confidence: 99%